Synthesis and Characterization of a Novel Nonionic Glucosamine-Based Surfactant and its Comparison with N-Methylglucamine Surfactant - Syedeh Enciyeh Rastegar Fatemi; Hadi Shafiei; Mohammad Majid Mojtahedi (شیمی کاربردی روز)
In this study, the synthesis and evaluation of surface and thermodynamics properties a novel non-ionic glucosamine-based surfactant (2-(dodecyloxy)-N-((2R,3R,4R,5S,6R)-2,4,5-trihydroxy-6-(hydroxymethyl)tetrahydro-2H-pyran-3-yl)acetamide (NGAS) is carried out and the comparison of the results with N-methylglucamine surfactant is reported. NGAS was synthesized via the facile and straightforward reaction of glucosamine with 2-(dodecyloxy)acetyl chloride in the presence of triethylamine. The surface tension of NGAS was determined by tensiometric methods. The surface properties including Critical Micelle Concentration (CMC), the efficiency of adsorption (pC20), the surface excess (Γmax) and the area occupied by each of the surfactant molecules (Amin) were investigated at 298.15 K in deionized water. The surface tension of water was reduced to about 41 mN.m-1 by using the surfactant at the concentration level of 2.06×10-3 molL-1. The thermodynamic parameters of micellization (ΔG°mic) and surface adsorption (ΔG°ads) were calculated from CMC data. The hydrophilicity and lipophilicity balance parameter (HLB) were obtained from the Griffin equation. According to the results, micellization and surface adsorption of this surfactant is a spontaneous process in aqueous solution. In addition, these results show that NGAS can be used as an emulsifier in oil-in-water emulsions.